The Concept of Quality in Higher Education: an Analysis of Quality as a Traveling Idea in the Strategic Documents of Higher Education Institutions - Tamutienė, Lina; Matkevičienė, Renata (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] The concept of quality is ambiguous and still under development – various studies in different fields of science expand the parameters of its analysis and open up a space for new insights. Recently, the researches in quality in higher education discuss quality issues in the context of changes that occur in the field of higher education. The role of the stakeholders in the quality assurance system could be linked to systemic procedural mechanisms – ways in which stakeholders are involved, how relationships among stakeholders and higher education institutions are developed. In scientific discourse, the role of stakeholders in quality assurance systems is linked to systemic procedural mechanisms and depends on the stakeholders’ interests. The scientific literature highlights the assumptions of quality as a traveling idea, but there is no research on the transfer of quality as an idea to the context of a higher education institution. This article analyzes the concept of quality in higher education through the theoretical perspective of Scandinavian institutionalism and examines the expression of quality as an idea in the strategic documents of higher education institutions. Indicators of quality applied for the analysis of the expression of quality as an idea in the strategic documents of higher education institution demonstrate the transfer of quality as an idea into the context of a higher education institution based on the interests of stakeholders. The roles of stakeholders in higher education institutions are different, so quality, as an idea, and its transfer to higher education institutions is assessed by different indicators, which express quality (quality as an idea) in higher education institutions based on the expectations of different stakeholders.